Peningkatan Kompetensi Kader Terhadap Kemandirian Dalam Penatalaksanaan Perdarahan Dalam Kehamilan - Suprapti, Suprapti; Setyarini, Didien Ika; Wulandari, Lisa Purbawaning (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2022)
Maternal mortality is still a challenge for the health system in Indonesia, one of the causes is bleeding during pregnancy as a result of the 3 Late (3 T) namely: late in making a decision/diagnosing, being late in getting to the referral place and being late in getting treatment. Detection of 3T bleeding in pregnant women can be done by anyone, including cadres as the spearhead in assisting pregnant women because of their presence in the community. This study aimed to analyse the competence of cadres in detecting and managing bleeding pregnant women according to their duties in the community to prevent 3T, one of which is animation media for bleeding pregnant women. The research design was a pre-experimental design using a quasi-experimental design using a pre-test-post-test design descriptive statistical analysis with a cross-sectional approach, a sample of 60 cadres who met the inclusion criteria (30 Parangargo and 30 Sidorahayu) in the working area of ??the Wagir Public Health Center, Malang Regency. The results of the pre-test-post-test between the control group and the treatment group showed the independence of cadres in the treatment of bleeding to perform 3T (p-value <0.001) and an increase in independence towards independence in treatment with the use of animation media between the control and treatment groups (p-value 0.001), with the acceptance of H1, an animation method that can provide a deeper understanding of the differences in blood flow, the color that occurs in early or late pregnancy, so that cadres in management are related to preventing 3 T according to the role of cadres in the community by escorting them to the location health services/ report to the regional midwife. Keywords: Cadre Competence, Management of Pregnancy Hemorrhagic